2008
DOI: 10.1016/j.clim.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells in common variable immunodeficiency: Clinical associations and sex differences

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous syndrome characterized by impaired antibody responses, recurrent infections, inflammatory, autoimmune and malignancyrelated conditions. We evaluated the relationship between memory B cell phenotype, sex, age at diagnosis, immunologic and clinical conditions in 105 CVID subjects from one medical center. Reduced numbers of switched memory B cells (cutoff ≤0.55% of B cells) were an independent risk factor of granulomas, autoimmune diseases and splenomegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 49 publications
(62 reference statements)
12
100
0
3
Order By: Relevance
“…+ population from CVID-derived B cells (mean, 1.69%) compared with the normal range (6.5-29.1%), which is in agreement with previous reports (2,35). Because of the very limited number of CD19 + B cells (range, 0.8-1.5 3 10 6 ) that could be obtained from the 35 ml of whole blood taken from each patient, it was impossible to subdivide the CD19 + fraction of cells into numbers that allow functional studies on IgG secretion.…”
Section: Discussionsupporting
confidence: 92%
“…+ population from CVID-derived B cells (mean, 1.69%) compared with the normal range (6.5-29.1%), which is in agreement with previous reports (2,35). Because of the very limited number of CD19 + B cells (range, 0.8-1.5 3 10 6 ) that could be obtained from the 35 ml of whole blood taken from each patient, it was impossible to subdivide the CD19 + fraction of cells into numbers that allow functional studies on IgG secretion.…”
Section: Discussionsupporting
confidence: 92%
“…Other known factors exacerbating CVID, such as chronic infections by EBV or CMV or malignancies, were also excluded. However, gender-related clinical differences between female and male CVID patients have been documented by two previous reports showing that male patients are generally more severely affected (10,40). Nevertheless, the precise co-modulating factors besides gender accounting for the difference between P1 and P2 remain unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In one such study, females were found to have significantly higher numbers of switched memory B cells in comparison with males (38). The significance of this finding is unknown.…”
Section: Immunologic Features Of Cvidmentioning
confidence: 99%